THE PERENCANAAN TEMPAT PEMROSESAN AKHIR SAMPAH DENGAN SISTEM SANITARY LANDFILL METODE CANYON DI KABUPATEN BONDOWOSO - Firra Rosariawari; Atikah Margi Utami (EnviroUS, 2022)
Final solid waste disposal place of Paguan which operates since 1993 still uses an open dumping system and requires additional land because it is no longer able to accommodate the increasing waste capacity over time. The purpose of this research is to plan a landfill with a Sanitary Landfill system according to existing regulations in Indonesia. This planning involves disposal zones planning, gas piping, leachate piping and other supporting facilities in the form of detailed engineering design, BOQ and RAB. The planning of this Sanitary Landfill TPA has an area about 4 hectares consisting of 2 disposal zones with an area of 0,78 Ha and 0,69 Ha. The landfill method uses the canyon method. According to the calculation, the life of this landfill is only 4,5 years starting from 2020 to 2024. The cost required to build the Bondowoso District Landfill is Rp. 24.929.391.437 (Twenty four billion nine hundred twenty-nine million three hundred ninety-one four hundred and thirty seven rupiah).